Synthesis of novel magnetic nanoparticles with urea or urethane moieties: Applications as catalysts in the Strecker synthesis of α‐aminonitriles. (24th May 2017) - Baghery, Saeed; Zolfigol, Mohammad Ali; Schirhagl, Romana; Hasani, Masoumeh; Stuart, Marc C.A.; Nagl, Andreas
Abstract : Four novel magnetic nanoparticle catalysts with urea or urethane moieties are reported. The silica‐coated magnetic nanoparticles were simply functionalized via addition of 3‐(triethoxysilyl)propylisocyanate (TESPIC), amine or amino alcohol. TESPIC with dual labile functional groups was used as a suitable precursor for the synthesis of urethane‐based catalysts. The newly synthesized catalysts were fully characterized using a variety of techniques. These functionalized magnetic nanoparticles were used as reusable catalysts in the Strecker synthesis of α‐aminonitrile derivatives under solvent‐free conditions at 50 °C. Abstract : Four novel biological‐based magnetic nanoparticle catalysts with urea or urethane moieties were synthesized via reaction of 3‐(triethoxysilyl)propylisocyanate, amine or amino alcohol and silica‐coated magnetic cores. Their catalytic application was also studied in the Strecker synthesis of α‐aminonitrile derivatives.